Pengaruh Work Family Conflict dan Emotional Exhaution terhadap Kinerja Perawat Wanita melalui Organizational Commitment pada Rumah Sakit Petrokimia Gresik - Dewi Ayu Lestari; Budiono Budiono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research aims to analyze the impact of work-family conflict and emotional exhaustion on female nurse performance through organizational commitment in Petrokimia Gresik Hospital. This study is using quantitative methods. The population in this study is 46 respondents. Saturation sampling is the sampling technique used in this study and obtained 46 respondents. Structural Equation Modeling (SEM) with the help of software SmartPLS is the analysis technique used in this study. The study found that work-family conflict has a significant negative effect on job performance. Work-family conflict has a significant negative effect on organizational commitment. Emotional exhaustion has a significant negative effect on job performance. Emotional exhaustion has a significant negative effect on organizational commitment. Organizational commitment has a significant positive effect on job performance. Work-family conflict has a significant result in job performance through organizational commitment. Emotional exhaustion has a significant result in job performance through organizational commitment.